Розширення частотного діапазону флікер-моделі для оцінювання коливань напруги - Курінний, Е. Г.; Дмитрієва, О. М.; Топчій, В. О. (Видавництво Національного університету «Львівська політехніка», 2007)
The problem of voltage oscillations is considered. It is shown that the existing flicker model underestimates requirements for voltage oscillations. It is proposed to expand the concept of flicker to the frequencies below 0.05 Hz. The permitted ranges of harmonic oscillations for the existing and proposed flicker models are compared